Liquid crystal polyester composition, pellet and molded article
The liquid crystal polyester composition with glass flakes and specific monomer units addresses the viscosity and electrical issues, enhancing fluidity and tensile properties of molded products.
Patent Information
- Application Number
- JP2023118293
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-30
AI Technical Summary
The presence of a large amount of inorganic filler in liquid crystal polyester compositions increases viscosity during melting, leading to poor molding and electrical characteristics of molded products.
A liquid crystal polyester composition containing glass flakes, first monomer units with a condensed aromatic ring, and second monomer units with a benzene ring, along with specific ratios and properties of glass flakes, to enhance fluidity and electrical characteristics.
The composition provides good fluidity during melting, excellent electrical characteristics, and improved tensile properties of molded products.
Smart Images

Figure 2025015124000001 
Figure 2025015124000002 
Figure 2025015124000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a liquid crystalline polyester composition, a pellet, and a molded article. [Background technology]
[0002] Liquid crystal polyesters are used in a variety of applications due to their high fluidity, heat resistance and dimensional accuracy.
[0003] Liquid crystal polyesters are usually used as liquid crystal polyester compositions containing fillers, etc., in order to satisfy the required properties depending on the application. For example, Patent Document 1 describes a liquid crystal polymer composition containing 15 mass % or more of a specific flat glass fiber and 20 mass % or more of a specific plate-like filler. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-268252 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, compositions containing a large amount of inorganic filler may have an increased viscosity when melted, resulting in poor moldability.
[0006] An object of the present disclosure is to provide a liquid crystal polyester composition having good flowability when melted, good electrical properties of a molded article, and good tensile properties of a molded article. Another object of the present disclosure is to provide a molded article formed from a liquid crystal polyester composition having excellent moldability, and having good electrical properties and good tensile properties. [Means for solving the problem]
[0007] The present disclosure provides, for example: [1] Contains liquid crystal polyester and glass flakes, The liquid crystal polyester contains a first monomer unit having a condensed aromatic ring and a second monomer unit having a benzene ring, The content of the glass flakes is 1 to 30 parts by mass with respect to 100 parts by mass of the liquid crystal polyester and the glass flakes in total, The density of the glass flakes is 1.8 g / cm 3 More than 2.5g / cm 3 A liquid crystal polyester composition, which is: [2] The liquid crystal polyester composition according to [1], wherein the condensed aromatic ring is a naphthalene ring. [3] The liquid crystal polyester composition according to [1] or [2], wherein the content of the first monomer unit is 50 mol % or more based on the total of all monomer units constituting the liquid crystal polyester. [4] The liquid crystal polyester composition according to any one of [1] to [3], wherein the glass flakes have a thickness of 0.1 μm or more and 2 μm or less. [5] The liquid crystal polyester composition according to any one of [1] to [4], wherein the glass flakes have an average particle size (D50) of 1 μm or more and 50 μm or less. [6] The liquid crystal polyester composition according to any one of [1] to [5], wherein the content of the inorganic filler other than the glass flakes is 25 mass % or less. [7] A pellet comprising the liquid crystal polyester composition according to any one of [1] to [6]. [8] A molded article comprising the liquid crystal polyester composition according to any one of [1] to [6], the molded article being a connector, a socket, a relay part, a coil bobbin, an optical pickup, an oscillator, a semiconductor package, an IC tray, a wafer carrier, a home electric appliance part, a lighting fixture part, an audio product part, a ferrule for an optical cable, a telephone part, a facsimile part, a modem part, a separation claw, a heater holder, an impeller, a fan gear, a gear, a bearing, a motor part, a motor case, an engine part, an engine room interior part, an electrical component part, an automobile interior part, a microwave cooking pot, a heat-resistant tableware, a floor material, a wall material, a beam, a pillar, a roof material, an aircraft part, a spacecraft part, a space equipment part, a nuclear reactor, a marine facility member, a cleaning tool, an optical equipment part, a valve, a pipe, a nozzle, a filter, a membrane, a medical equipment part, a medical material, a sensor part, a sanitary equipment, a sporting goods, or a leisure goods. Effect of the Invention
[0008] According to the present disclosure, it is possible to provide a liquid crystal polyester composition having good fluidity when melted, good electrical properties of a molded article, and good tensile properties of a molded article. In addition, according to the present disclosure, it is possible to provide a molded article formed from a liquid crystal polyester composition having excellent moldability and having good electrical properties and good tensile properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Preferred embodiments of the present disclosure will now be described in detail.
[0010] The liquid crystal polyester composition of this embodiment (hereinafter also simply referred to as "liquid crystal polyester composition") contains a liquid crystal polyester and glass flakes. The liquid crystal polyester contains a first monomer unit having a condensed aromatic ring and a second monomer unit having a benzene ring. The content of the glass flakes is 1 to 30 parts by mass with respect to 100 parts by mass of the total of the liquid crystal polyester and the glass flakes. In this embodiment, the liquid crystal polyester composition may or may not contain an inorganic filler other than the glass flakes, but the content of the inorganic filler other than the glass flakes is 10% by mass or less.
[0011] The liquid crystal polyester composition of the present embodiment has good fluidity when melted, good electrical properties of a molded article, and good tensile properties (tensile strength, nominal tensile strain at break) of a molded article.
[0012] Although the reason why the above-mentioned effect is achieved is not entirely clear, the present inventors believe it to be as follows. Liquid crystal polyester is a rigid rod-like polymer, and when used alone, it rotates in various directions and is difficult to align in the flow direction. In contrast, in a liquid crystal polyester composition containing a certain amount of glass flakes, the faces of the glass flakes are aligned parallel to the flow direction, so that the liquid crystal polyester is oriented along the faces of the glass flakes, and the flow direction and the direction of the polymer chains of the liquid crystal polyester are aligned, which is thought to improve the fluidity. In addition, it is thought that the parallel alignment of the glass flakes forms pseudo-flow paths, which makes it easier to orient the polymer chains of the liquid crystal polyester.
[0013] In addition, in this embodiment, since the liquid crystal polyester contains a first monomer unit having a condensed aromatic ring, the polymer chain of the liquid crystal polyester is likely to be more rigid and rod-like. Furthermore, since the condensed aromatic ring has high planarity, it is likely to be aligned parallel to the surface of the glass flake, which promotes flow and exhibits good interaction with the surface of the flake, improving the mechanical properties. In addition, by using glass flakes with a lower density than general glass flakes, the density of the liquid crystal polyester and the density of the glass flakes become closer, and the alignment of the liquid crystal polymers is less likely to be hindered, improving the mechanical properties.
[0014] The liquid crystal polyester may be any polyester that exhibits liquid crystallinity in a molten state. The liquid crystal polyester composition may contain only one type of liquid crystal polyester, or may contain two or more types of liquid crystal polyester.
[0015] The flow initiation temperature of the liquid crystal polyester may be, for example, 250° C. or more, or 270° C. or more. The flow initiation temperature of the liquid crystal polyester may be, for example, 400° C. or less, 360° C. or less, or 340° C. or less. That is, the flow initiation temperature of the liquid crystal polyester may be, for example, 250°C or more and 400°C or less, 250°C or more and 360°C or less, 250°C or more and 340°C or less, 270°C or more and 400°C or less, 270°C or more and 360°C or less, or 270°C or more and 340°C or less.
[0016] In this specification, the flow initiation temperature of the liquid crystal polyester is measured using a flow tester, and the liquid crystal polyester is subjected to a pressure of 9.8 MPa (100 kg / cm 2 ) while heating at a rate of 4°C / min under a load of 1000 g / s, and extruding the molten liquid crystalline polyester from a nozzle with an inner diameter of 1 mm and a length of 10 mm, the temperature at which it reaches a viscosity of 4800 Pa s (48,000 poise).
[0017] The liquid crystal polyester has a constituent unit (also called a monomer unit) derived from a raw material monomer. The liquid crystal polyester may have a main monomer unit (for example, 90 mol% or more, 95 mol% or more, or 99 mol% or more of the monomer units relative to the total of all monomer units, preferably all monomer units) that is derived from an aromatic compound. The liquid crystal polyester in which all monomer units are derived from an aromatic compound is also called a wholly aromatic liquid crystal polyester.
[0018] The liquid crystal polyester has a first monomer unit having a condensed aromatic ring and a monomer unit having a benzene ring. The liquid crystal polyester may have one or more types of the first monomer unit. The liquid crystal polyester may also have one or more types of the second monomer unit. The second monomer unit may be a monomer unit having a benzene ring and not having a condensed aromatic ring.
[0019] The first monomer unit may be a monomer unit derived from an aromatic compound (1) having a condensed aromatic ring, and the second monomer unit may be a monomer unit derived from an aromatic compound (2) having a benzene ring.
[0020] In this specification, the term "origin" means that in the monomer unit of the liquid crystal polyester formed by polymerization of the raw material monomer, the chemical structure of the functional group that contributes to polymerization of the raw material monomer has changed, but other structural changes have not occurred. The term "origin" here is a concept that also includes the case where the monomer is derived from a polymerizable derivative of the raw material monomer (for example, a compound obtained by converting the functional group that contributes to polymerization of the raw material monomer into another polymerizable group).
[0021] Examples of the first monomer unit include a monomer unit derived from an aromatic hydroxycarboxylic acid (1-1) having a condensed aromatic ring (hereinafter also referred to as a monomer unit (1-1)), a monomer unit derived from an aromatic dicarboxylic acid (1-2) having a condensed aromatic ring (hereinafter also referred to as a monomer unit (1-2)), and a monomer unit derived from an aromatic diol (1-3) having a condensed aromatic ring (hereinafter also referred to as a monomer unit (1-3)).
[0022] Examples of the second monomer unit include a monomer unit derived from an aromatic hydroxycarboxylic acid (2-1) (hereinafter also referred to as a monomer unit (2-1)), a monomer unit derived from an aromatic dicarboxylic acid (2-2) (hereinafter also referred to as a monomer unit (2-2)), and a monomer unit derived from an aromatic diol (2-3) (hereinafter also referred to as a monomer unit (2-3)).
[0023] Examples of the fused aromatic ring contained in the first monomer unit include a naphthalene ring, an anthracene ring, a phenanthrene ring, a tetracene ring, a pyrene ring, a triphenylene ring, a perylene ring, and a fluorene ring. Among these, a naphthalene ring is preferred from the viewpoints of availability and cost.
[0024] Examples of the monomer units contained in the liquid crystal polyester include a monomer unit represented by the following formula (I) (hereinafter also referred to as monomer unit (I)), a monomer unit represented by the following formula (II) (hereinafter also referred to as monomer unit (II)), and a monomer unit represented by the following formula (III) (hereinafter also referred to as monomer unit (III)). -O-Ar 1 -CO- (I) -CO-Ar 2 -CO- (II) -X-Ar 3 -Y- (III) [In the formula, Ar 1 , Ar 2 and Ar 3 each independently represents a phenylene group, a biphenylene group, a condensed polycyclic aromatic hydrocarbon group, or a group represented by formula (IV). 1 , Ar 2and Ar 3 may be substituted with a halogen atom, an alkyl group or an aryl group. X and Y each independently represent an oxygen atom or an imino group (-NH-). -Ar 4 -Z-Ar 5 - (IV) [In the formula, Ar 4 and Ar 5 each independently represents a phenylene group or a condensed polycyclic aromatic hydrocarbon group; Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkanediyl group.
[0025] The phenylene group may be a 1,4-phenylene group or a 1,3-phenylene group, preferably a 1,4-phenylene group.
[0026] The biphenylene group may be a 4,4'-biphenylylene group.
[0027] The condensed polycyclic aromatic hydrocarbon group is a group in which two hydrogen atoms are removed from a condensed polycyclic aromatic hydrocarbon. Examples of the condensed polycyclic aromatic hydrocarbon include naphthalene, anthracene, phenanthrene, tetracene, pyrene, triphenylene, perylene, and fluorene. Among these, naphthalene is preferred from the viewpoints of availability and cost.
[0028] The condensed polycyclic aromatic hydrocarbon group may be a naphthylene group. The naphthylene group may be a 2,6-naphthylene group or a 2,7-naphthylene group, and is preferably a 2,6-naphthylene group.
[0029] Examples of the halogen atom as a substituent include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0030] The alkyl group as a substituent may be linear, branched or cyclic. The alkyl group may be, for example, an alkyl group having 1 to 10 carbon atoms. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, an s-butyl group, a t-butyl group, an n-hexyl group, a 2-ethylhexyl group, an n-octyl group, and an n-decyl group.
[0031] The aryl group as a substituent may be a single ring or a condensed ring. The aryl group may be, for example, an aryl group having 6 to 20 carbon atoms. Examples of the aryl group include a phenyl group, an o-tolyl group, an m-tolyl group, a p-tolyl group, a 1-naphthyl group, and a 2-naphthyl group. The aryl group may be a group in which a hydrogen atom of an aromatic ring is substituted with an alkyl group, such as a tolyl group.
[0032] Ar 1 , Ar 2 and Ar 3 The number of substituents that the has may be, for example, 0 to 2, may be 0 or 1, or may be 0.
[0033] X and Y are preferably oxygen atoms.
[0034] The alkanediyl group in Z may be linear or branched. The alkanediyl group may be an alkanediyl group having 1 to 10 carbon atoms. Examples of the alkanediyl group include a methylene group, an ethanediyl group, a propanediyl group (e.g., a propane-2,2-diyl group), a butanediyl group, and an octanediyl group (e.g., an octane-3,3-diyl group).
[0035] Z is preferably an oxygen atom, a sulfur atom, a methylene group, an ethanediyl group, or a propanediyl group, and more preferably an oxygen atom.
[0036] The first monomer unit is a monomer unit represented by formula (I) (Ar 1 is a condensed polycyclic aromatic hydrocarbon group, or Ar 4 and Ar 5at least one of which is a condensed polycyclic aromatic hydrocarbon group, may be a group represented by formula (IV), and the monomer unit represented by formula (II) (Ar 2 is a condensed polycyclic aromatic hydrocarbon group, or Ar 4 and Ar 5 at least one of which is a condensed polycyclic aromatic hydrocarbon group, a group represented by formula (IV); 2 is a condensed polycyclic aromatic hydrocarbon group, or Ar 4 and Ar 5 at least one of which is a condensed polycyclic aromatic hydrocarbon group represented by formula (IV).
[0037] The first monomer unit may be a monomer unit derived from an aromatic compound (1) having a condensed aromatic ring. Examples of the aromatic compound (1) include 2-hydroxy-6-naphthoic acid, 2,6-naphthalenedicarboxylic acid, 2,6-dihydroxynaphthalene, 2-hydroxy-3-naphthoic acid, 1-hydroxy-5-naphthoic acid, and 2,7-naphthalenediol.
[0038] The second monomer unit is a monomer unit represented by formula (I) (Ar 1 is a phenylene group, a biphenylene group, or Ar 4 and Ar 5 is a phenylene group), and the monomer unit represented by formula (II) (Ar 2 is a phenylene group, a biphenylene group, or Ar 4 and Ar 5 is a phenylene group), and the monomer unit represented by formula (III) (Ar 3 is a phenylene group, a biphenylene group, or Ar 4 and Ar 5 may be a group represented by formula (IV) in which R is a phenylene group.
[0039] The second monomer unit may be a monomer unit derived from an aromatic compound (2) having a benzene ring but no condensed aromatic ring. Examples of the aromatic compound (2) include p-hydroxybenzoic acid, terephthalic acid, hydroquinone, isophthalic acid, and 4,4'-biphenol.
[0040] In the liquid crystal polyester, the content of the first monomer unit may be, for example, 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, or 70 mol% or more, based on the total of all monomer units constituting the liquid crystal polyester. When the content of the first monomer unit is high, the dielectric properties tend to be improved. In addition, the content of the first monomer unit may be, for example, 90 mol% or less, 85 mol% or less, or 80 mol% or less, based on the total of all monomer units constituting the liquid crystal polyester. This tends to improve moldability and processability at low temperatures. That is, the content of the first monomer unit may be, for example, 20 mol% or more and 90 mol% or less, 20 mol% or more and 85 mol% or less, 20 mol% or more and 80 mol% or less, 30 mol% or more and 90 mol% or less, 30 mol% or more and 85 mol% or less, 30 mol% or more and 80 mol% or less, 40 mol% or more and 40 mol% or less, 40 mol% or more and 85 mol% or less, 40 mol% or more and 80 mol% or less, 50 mol% or more and 90 mol% or less, 50 mol% or more and 85 mol% or less, 50 mol% or more and 80 mol% or less, 60 mol% or more and 90 mol% or less, 60 mol% or more and 85 mol% or less, 60 mol% or more and 80 mol% or less, 70 mol% or more and 90 mol% or less, 70 mol% or more and 85 mol% or less, or 70 mol% or more and 80 mol% or less.
[0041] In the liquid crystal polyester, the content of the second monomer unit may be, for example, 10 mol% or more, 15 mol% or more, or 20 mol% or more, based on the total of all monomer units constituting the liquid crystal polyester. This tends to be advantageous in terms of cost. In addition, the content of the second monomer unit may be, for example, 80 mol% or less, 70 mol% or less, 60 mol% or less, 50 mol% or less, 40 mol% or less, or 30 mol% or less, based on the total of all monomer units constituting the liquid crystal polyester. That is, the content of the second monomer unit may be, for example, 10 mol% or more and 80 mol% or less, 10 mol% or more and 70 mol% or less, 10 mol% or more and 60 mol% or less, 10 mol% or more and 50 mol% or less, 10 mol% or more and 40 mol% or less, 10 mol% or more and 30 mol% or less, 15 mol% or more and 80 mol% or less, 15 mol% or more and 70 mol% or less, 15 mol% or more and 60 mol% or less, 15 mol% or more and 50 mol% or less, 15 mol% or more and 40 mol% or less, 15 mol% or more and 30 mol% or less, 20 mol% or more and 80 mol% or less, 20 mol% or more and 70 mol% or less, 20 mol% or more and 60 mol% or less, 20 mol% or more and 50 mol% or less, 20 mol% or more and 40 mol% or less, or 20 mol% or more and 30 mol% or less.
[0042] In the liquid crystal polyester, the total amount of the first monomer unit and the second monomer unit may be, for example, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% relative to the sum of all monomer units constituting the liquid crystal polyester.
[0043] The liquid crystal polyester may be a polymer having two or more kinds of monomer units (I), or may be a polymer having monomer units (I), monomer units (II) and monomer units (III).
[0044] When the liquid crystal polyester has the monomer unit (I), the monomer unit (II) and the monomer unit (III), the content of the monomer unit (I) may be, for example, 30 mol% or more, 40 mol% or more, 45 mol% or more, 50 mol% or more, or 55 mol% or more, based on the total of all the monomer units of the liquid crystal polyester. When the liquid crystal polyester has the monomer unit (I), the monomer unit (II) and the monomer unit (III), the content of the monomer unit (I) may be, for example, 80% or less, or 70% or less, based on the total of all the monomer units of the liquid crystal polyester. That is, when the liquid crystal polyester has monomer unit (I), monomer unit (II) and monomer unit (III), the content of monomer unit (I) may be, for example, 30 mol% or more and 80 mol% or less, 30 mol% or more and 70 mol% or less, 40 mol% or more and 80 mol% or less, 40 mol% or more and 70 mol% or less, 45 mol% or more and 80 mol% or less, 45 mol% or more and 70 mol% or less, 50 mol% or more and 80 mol% or less, 50 mol% or more and 70 mol% or less, 55 mol% or more and 80 mol% or less, or 55 mol% or more and 70 mol% or less.
[0045] When the liquid crystal polyester has the monomer unit (I), the monomer unit (II) and the monomer unit (III), the content of the monomer unit (II) and the content of the monomer unit (III) may be, for example, 35 mol% or less, or 30 mol% or less, based on the total of all monomer units of the liquid crystal polyester. When the liquid crystal polyester has the monomer unit (I), the monomer unit (II) and the monomer unit (III), the content of the monomer unit (II) and the content of the monomer unit (III) may be, for example, 5 mol% or more, 10 mol% or more, or 15 mol% or more, based on the total of all monomer units of the liquid crystal polyester. That is, when the liquid crystal polyester has monomer unit (I), monomer unit (II) and monomer unit (III), the content of monomer unit (II) and the content of monomer unit (III) may be, for example, 5 mol% or more and 35 mol% or less, 5 mol% or more and 30 mol% or less, 10 mol% or more and 35 mol% or less, 10 mol% or more and 30 mol% or less, 15 mol% or more and 35 mol% or less, or 15 mol% or more and 30 mol% or less, relative to the sum of all monomer units of the liquid crystal polyester.
[0046] The liquid crystal polyester may have monomer units other than the monomer unit (I), the monomer unit (II) and the monomer unit (III), and the number of such monomer units may be 10 mol % or less, 5 mol % or less, 2 mol % or less, or 1 mol % or less, or may be 0 mol % or less, relative to the total number of all monomer units of the liquid crystal polyester.
[0047] In this specification, the number of each monomer unit contained in the liquid crystal polyester is determined by the analysis method described in JP 2000-19168 A. Specifically, the liquid crystal polyester is depolymerized by reacting it with a lower alcohol in a supercritical state, and the depolymerization product (monomer that derives each monomer unit) is quantified by liquid chromatography, whereby the number of each monomer unit relative to the total monomer units can be calculated.
[0048] The liquid crystal polyester can be produced by polymerizing raw material monomers corresponding to the monomer units constituting the liquid crystal polyester, for example, according to the method described in Japanese Patent No. 6439027.
[0049] The dielectric loss tangent of the liquid crystal polyester at 10 GHz may be, for example, 0.002 or less, preferably 0.0015 or less, more preferably 0.0012 or less, which makes it easier to obtain a liquid crystal polyester composition having a suitable dielectric loss tangent as described below.
[0050] The liquid crystal polyester may have a relative dielectric constant at 10 GHz of, for example, 4.0 or less, or 3.8 or less. The liquid crystal polyester may have a relative dielectric constant at 10 GHz of, for example, 2.8 or more, or 3.0 or more.
[0051] In this specification, the dielectric loss tangent and the relative dielectric constant at 10 GHz of the liquid crystal polyester are measured by the following method. Using an injection molding machine (FANUC Corporation, ROBOSHOT S-2000i 30B), a test piece with a width of 50 mm, length of 50 mm, and thickness of 0.5 mm is obtained using liquid crystal polyester pellets as the molding material under the conditions of a cylinder temperature of 335°C, a mold temperature of 130°C, and an injection speed of 50 mm / s. The relative dielectric constant and dielectric loss tangent at 10 GHz of the obtained test piece are measured using a vector network analyzer (Keysight Technologies, Inc., N5290A) and a split cylinder resonator (EM Lab, Inc., CR710). The measurement environment is 23°C and 50% RH.
[0052] The glass flakes are scaly glass fillers.
[0053] The thickness of the glass flakes may be, for example, 0.1 μm or more. From the viewpoint of increasing the strength of the glass flakes and preventing the glass flakes from being broken, thereby making it easier to maintain the effect of reducing viscosity, the thickness may be 0.2 μm or more, 0.3 μm or more, or 0.4 μm or more. The thickness of the glass flakes may be, for example, 2 μm or less, and from the viewpoint of being easily aligned in the flow direction and obtaining the above-mentioned effect more significantly, the thickness may be 1.8 μm or less, 1.6 μm or less, or 1.3 μm or less.
[0054] In this specification, the thickness of the glass flakes is measured by the following method. Glass flakes are observed under a scanning electron microscope (SEM), and the thickness of 10 glass flakes randomly selected from the obtained image is measured and the average value is calculated. Since the thickness of glass flakes does not usually change during the granulation process, the measurement may be performed on glass flakes before granulation, or the ash remaining after thermally decomposing the organic components of pellets or molded products may be measured.
[0055] The average particle size (D50) of the glass flakes may be, for example, 2 μm or more, and from the viewpoint of being easily aligned in the flow direction and obtaining the above-mentioned effects more significantly, it may be 2.4 μm or more, 2.7 μm or more, or 3 μm or more. The average particle size (D50) of the glass flakes may be, for example, 50 μm or less, and from the viewpoint of being easily manufactured into small or thin-walled molded products, it may be 40 μm or less, 35 μm or less, or 30 μm or less. In general, the D50 of the glass flakes changes during the granulation and molding processes, so the organic components of the pellets or molded products are thermally decomposed and the ash remaining is measured.
[0056] The ratio of the thickness to the average particle size (D50) of the glass flakes (thickness / average particle size (D50)) may be, for example, 3 or more, and from the viewpoint of having a good flake shape and obtaining the above-mentioned effects more significantly, it may be 3.5 or more, 4 or more, or 4.5 or more. The ratio of the thickness to the average particle size (D50) of the glass flakes (thickness / average particle size (D50)) may be, for example, 500 or less, and from the viewpoint of facilitating the production of small or thin-walled molded products, it may be 200 or less, 100 or less, or 50 or less.
[0057] In this specification, the average particle size (D50) of the glass flakes indicates a value measured by the following method. The glass flakes are measured by a laser diffraction method to determine the average particle size (D50). Specifically, the glass flakes are dispersed in water, and the particle size is measured under the following measurement conditions using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Horiba Co., Ltd., "LA-950V2"). [Measurement conditions] Particle refractive index: 1.56 Dispersion medium: water Dispersion medium refractive index: 1.33
[0058] The density of the glass flakes is 1.8 g / cm 3 More than 1.85g / cm 3 More than 1.9g / cm 3 or more than 1.95g / cm 3 The density of the glass flakes may be 2.5 g / cm or more. 3 From the viewpoint of being closer to the density of the liquid crystal polyester, being easier to be oriented in the composition, and being able to obtain the above-mentioned effects more significantly, it is 2.45 g / cm or less. 3 Below, 2.4g / cm 3 Less than or equal to 2.35g / cm 3 It may be the following.
[0059] In this specification, the density of the glass flakes refers to a value calculated from the following formula based on the measurement results by the pycnometer method of JIS K0061. When the glass flakes contain air bubbles, the glass flakes may be crushed before measurement. Water is used as the solution. When air bubbles are contained at the interface between the glass flakes and the water, a small amount of a surfactant may be added to the water to remove the air bubbles. Density = {(Wb-Wa) / (Wb-Wa-Wc+Wd)} × density of solution [In the formula, Wa is the weight of the pycnometer, Wb is the weight of (pycnometer + sample), Wc is the weight of (pycnometer + sample + weight of solution up to the pycnometer mark), and Wc is the weight of (pycnometer + weight of solution up to the pycnometer mark)]
[0060] The glass constituting the glass flakes may be, for example, SL glass (manufactured by Nippon Sheet Glass Co., Ltd.), LLD glass (manufactured by Nippon Sheet Glass Co., Ltd.), D glass, etc., and from the viewpoint of easily achieving the above-mentioned suitable density and of having good dielectric properties, SL glass (manufactured by Nippon Sheet Glass Co., Ltd.) and LLD glass (manufactured by Nippon Sheet Glass Co., Ltd.) are preferred, with SL glass (manufactured by Nippon Sheet Glass Co., Ltd.) being more preferred.
[0061] The content of glass flakes in the liquid crystal polyester composition is 1 part by mass or more, may be 2 parts by mass or more, or may be 5 parts by mass or more, based on 100 parts by mass of the total of liquid crystal polyester and glass flakes. By increasing the content of glass flakes, the flexibility of the molded product of the liquid crystal polyester composition tends to be improved. In addition, the content of glass flakes in the liquid crystal polyester composition may be 30 parts by mass or less, 25 parts by mass or less, 20 parts by mass or less, or 15 parts by mass or less, based on 100 parts by mass of the total of liquid crystal polyester and glass flakes. By decreasing the content of glass flakes, the good flowability during melting tends to be improved.
[0062] The liquid crystal polyester composition may further contain other components in addition to the liquid crystal polyester and the glass flakes.
[0063] For example, the liquid crystal polyester composition may contain one or more resins other than the liquid crystal polyester, such as polyolefin, cyclic polyolefin, polyvinyl chloride, polysulfone, (meth)acrylic resin, polyphenylene ether resin, polyacetal resin, polyamide resin, imide resin, cellulose resin, polyether ether ketone resin, fluororesin, polycarbonate resin, styrene-based resin, and thermosetting resin.
[0064] The liquid crystal polyester composition may further contain an inorganic filler, a colorant, a dispersant, a plasticizer, an antioxidant, a curing agent, a flame retardant, a heat stabilizer, an ultraviolet absorber, an antistatic agent, a surfactant, a lubricant, a release agent, and the like.
[0065] However, the content of inorganic fillers other than glass flakes in the liquid crystal polyester composition may be, for example, 25% by mass or less, preferably 20% by mass or less, based on the total amount of the liquid crystal polyester composition. By reducing the content of inorganic fillers other than glass flakes, the inorganic fillers are prevented from interfering with the relationship between the glass flakes and the polymer chains of the liquid crystal polyester, and the above-mentioned effects are more prominently obtained. From the viewpoint of obtaining the above-mentioned effects more prominently, the content of inorganic fillers other than glass flakes may be 15% by mass or less, 10% by mass or less, or 5% by mass or less, based on the total amount of the liquid crystal polyester composition, or may be 0% by mass.
[0066] The liquid crystal polyester composition has excellent fluidity when melted, and therefore can be suitably used as a molding material. The liquid crystal polyester composition may be used, for example, in the form of pellets.
[0067] The molded article of the embodiment comprises the liquid crystal polyester composition described above.The molded article of the embodiment may be connector, socket, relay parts, coil bobbin, optical pickup, oscillator, semiconductor package, IC tray, wafer carrier, household electrical appliance parts, lighting equipment parts, audio product parts, ferrule for optical cable, telephone parts, facsimile parts, modem parts, separation claw, heater holder, impeller, fan gear, gear, bearing, motor parts, motor case, engine parts, engine room parts, electrical equipment parts, automobile interior parts, microwave cooking pot, heat-resistant tableware, floor material, wall material, beam, pillar, roof material, aircraft parts, spacecraft parts, space equipment parts, nuclear reactor, marine facility parts, cleaning tool, optical equipment parts, valves, pipes, nozzles, filters, membranes, medical equipment parts, medical materials, sensor parts, sanitary equipment, sports goods, or leisure goods.
[0068] The molded article of the present embodiment can be obtained, for example, by molding the liquid crystal polyester composition described above into a desired shape and subjecting it to processing treatment as necessary.
[0069] The molding method for the molded product is preferably melt molding, and examples of the melt molding method include injection molding, extrusion molding, compression molding, blow molding, vacuum molding, foam molding, and press molding.
[0070] Although the preferred embodiments of the present disclosure have been described above, the present disclosure is not limited to the above embodiments. EXAMPLES
[0071] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following, percentages and parts that represent the content or amount used are based on mass unless otherwise specified.
[0072] (Example 1-1) (1) Manufacture of liquid crystal polyester (LCP1) Into a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 1035.0g (5.5 mol) of 2-hydroxy-6-naphthoic acid, 378.3g (1.75 mol) of 2,6-naphthalenedicarboxylic acid (Ueno Pharmaceutical Co., Ltd.), 83.1g (0.5 mol) of terephthalic acid, 255.2g of hydroquinone, 1226.87g (12 mol) of acetic anhydride, and 0.17g of 1-methylimidazole as a catalyst were placed. After the inside of the reactor was sufficiently replaced with nitrogen gas, the temperature was raised to 140°C over 1 hour under a nitrogen gas flow, and the temperature was maintained and refluxed for 1 hour. The temperature was then raised to 310°C over 4 hours and 35 minutes while distilling off the by-product acetic acid, and the reaction was deemed to have ended when an increase in torque was observed, and the contents were removed. The flow-start temperature of the obtained solid was 270°C. The obtained solid was cooled to room temperature and pulverized in a coarse pulverizer, and then heated from room temperature to 250°C over 1 hour in a nitrogen atmosphere, heated from 250°C to 286°C over 7 hours and 40 minutes, and held at 286°C for 6 hours, to obtain a powdered liquid crystal polyester (LCP1).
[0073] The flow initiation temperature of the liquid crystal polyester (LCP1) was measured by the following method and found to be 311°C. <Measurement of flow start temperature> Using a flow tester (Shimadzu Corporation, CFT-500 model), approximately 2 g of liquid crystal polyester pellets were filled into a cylinder equipped with a die having a nozzle with an inner diameter of 1 mm and a length of 10 mm, and the flow rate was measured at 9.8 MPa (100 kg / cm 2 The liquid crystal polyester was melted and extruded from the nozzle while heating at a rate of 4°C / min under a load of 1.5 g, and the temperature (FT) at which the viscosity reached 4800 Pa·s (48000 P) was measured and defined as the flow initiation temperature. "About 2 g" can be estimated as 2 g ± 0.1 g.
[0074] The liquid crystal polyester (LCP1) had a relative dielectric constant of 3.5 and a dielectric dissipation factor of 0.00081 at 10 GHz.
[0075] (2) Preparation of glass flakes (G1) As glass flakes, the average particle size (D50) is 7.2 μm, the thickness is 0.89 μm, and the density is 2.03 g / cm 3 Glass flakes (G1) (manufactured by Nippon Sheet Glass Co., Ltd.) composed of SL glass (silica content of 97% by mass or more) were prepared.
[0076] (3) Production of Liquid Crystal Polyester Composition and Pellets A liquid crystal polyester composition was obtained by mixing the liquid crystal polyester (LCP1) and the glass flakes (G1) in a mass ratio of 97:3. The liquid crystal polyester composition was then granulated at a cylinder temperature of 320°C using a twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd., PCM-30) to obtain pellets of the liquid crystal polyester composition.
[0077] (4) Evaluation of liquid crystal polyester composition and molded product The melt viscosity, tensile strength, nominal tensile strain at break, relative dielectric constant and dielectric loss tangent were determined by the following methods. The average particle size (D50) of the glass flakes in the pellets was also determined by the following methods. The results are shown in Table 1. <Evaluation of fluidity when melted> Using a capillary rheometer (Capillograph 1D, manufactured by Toyo Seiki Seisakusho Co., Ltd.), a capillary with an inner diameter of 0.5 mm and a length of 10 mm was attached to the tip of the cylinder, and pellets of the liquid crystal polyester composition were melted in the cylinder heated to 340° C. and extruded from the nozzle. The viscosity of the extruded liquid crystal polyester composition at a shear rate of 1000 / sec was measured, and the viscosity was evaluated as the melt viscosity of the liquid crystal polyester composition.
[0078] <Measurement of tensile strength and nominal tensile breaking strain> Using an injection molding machine (Nissei Plastic Industrial Co., Ltd., PNX-40-5A), the liquid crystal polyester composition pellets were used as the molding material to injection mold ASTM D638 dumbbell-shaped test pieces Type IV (thickness 2.5 mm) under the conditions of a cylinder temperature of 340°C, a mold temperature of 130°C, and an injection speed of 75 mm / s. Tensile tests were performed on five samples of the obtained dumbbell test pieces using a tensile tester (A&D Co., Ltd., Tensilon RTG-1310) at a chuck distance of 50 mm, a crosshead speed of 10 mm / min, and a test temperature of 23°C, and the elongation at that time was measured, and the average values of the tensile strength at break (MPa) and nominal tensile break strain (%) of the five samples were calculated. The nominal tensile breaking strain was calculated by the following formula: Nominal tensile breaking strain (%) = (L-Lo) / Lo x 100 Lo: Length of chuck distance before test (mm) L: Distance between chucks at break (mm)
[0079] <Evaluation of dielectric properties> Using an injection molding machine (FANUC Corporation, ROBOSHOT S-2000i 30B), a test piece having a width of 50 mm, a length of 50 mm, and a thickness of 0.5 mm was obtained using pellets of the liquid crystal polyester composition as a molding material under the conditions of a cylinder temperature of 335°C, a mold temperature of 130°C, and an injection speed of 50 mm / s. The relative dielectric constant and dielectric loss tangent at 10 GHz of the obtained test piece were measured using a vector network analyzer (Keysight Technologies, Inc., N5290A) and a split cylinder resonator (EM Lab, Inc., CR710). Measurement environment: 23℃, 50% RH
[0080] <Measurement of the average particle size (D50) of glass flakes> The pellets were heated at 600°C for 3 hours to remove the organic components, and the glass flakes were collected. The average particle size (D50) of the collected glass flakes was determined by the method described above.
[0081] (Example 1-2) A liquid crystal polyester composition and pellets were produced in the same manner as in Example 1-1, except that the ratio of liquid crystal polyester (LCP1) to glass flakes (G1) was changed from 97: 3 to 92: 8. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 1.
[0082] (Examples 1-3) A liquid crystal polyester composition and pellets were produced in the same manner as in Example 1-1, except that the ratio of liquid crystal polyester (LCP1) to glass flakes (G1) was changed from 97: 3 to 80: 20. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 1.
[0083] (Comparative Example 1-1) A liquid crystal polyester composition and pellets were produced in the same manner as in Example 1-1, except that glass flakes (G1) were not added and only liquid crystal polyester (LCP1) was used. The obtained pellets were evaluated in the same manner as in Example 1-1, and the results are shown in Table 1.
[0084] [Table 1]
[0085] (Example 2-1) (1) Preparation of glass flakes (G2) As glass flakes, the average particle size (D50) is 27 μm, the thickness is 0.77 μm, and the density is 2.00 g / cm 3 Glass flakes (G2) (manufactured by Nippon Sheet Glass Co., Ltd.) composed of SL glass were prepared.
[0086] (2) Preparation and Evaluation of Liquid Crystal Polyester Composition and Pellets The liquid crystal polyester (LCP1) and the glass flakes (G2) were mixed in a mass ratio of 92:8 to obtain a liquid crystal polyester composition. The liquid crystal polyester composition was then granulated at a cylinder temperature of 320°C using a twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd., PCM-30) to obtain pellets of the liquid crystal polyester composition. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 2.
[0087] (Example 2-2) (1) Preparation of glass flakes (G3) As glass flakes, the average particle size (D50) is 11 μm, the thickness is 0.44 μm, and the density is 2.13 g / cm 3 Glass flakes (G3) (manufactured by Nippon Sheet Glass Co., Ltd.) composed of LLD glass (silica content: 45 to 60 mass %) were prepared.
[0088] (2) Preparation and Evaluation of Liquid Crystal Polyester Composition and Pellets The liquid crystal polyester (LCP1) and the glass flakes (G3) were mixed in a mass ratio of 92:8 to obtain a liquid crystal polyester composition. The liquid crystal polyester composition was then granulated at a cylinder temperature of 320°C using a twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd., PCM-30) to obtain pellets of the liquid crystal polyester composition. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 2.
[0089] (Example 2-3) (1) Preparation of glass flakes (G4) As glass flakes, the average particle size (D50) is 22 μm, the thickness is 0.71 μm, and the density is 2.33 g / cm 3 Glass flakes (G4) (manufactured by Nippon Sheet Glass Co., Ltd.) made of LLD glass were prepared.
[0090] (2) Preparation and Evaluation of Liquid Crystal Polyester Composition and Pellets The liquid crystal polyester (LCP1) and the glass flakes (G4) were mixed in a mass ratio of 92:8 to obtain a liquid crystal polyester composition. The liquid crystal polyester composition was then granulated at a cylinder temperature of 320°C using a twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd., PCM-30) to obtain pellets of the liquid crystal polyester composition. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 2.
[0091] (Comparative Example 2-1) (1) Preparation of glass flakes (g1) As glass flakes, the average particle size (D50) is 57 μm, the thickness is 0.56 μm, and the density is 2.71 g / cm 3 Glass flakes (g1) (manufactured by Nippon Sheet Glass Co., Ltd.) made of E glass were prepared.
[0092] (2) Preparation and Evaluation of Liquid Crystal Polyester Composition and Pellets The liquid crystal polyester (LCP1) and the glass flakes (g1) were mixed in a mass ratio of 92:8 to obtain a liquid crystal polyester composition. The liquid crystal polyester composition was then granulated at a cylinder temperature of 320°C using a twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd., PCM-30) to obtain pellets of the liquid crystal polyester composition. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 2.
[0093] [Table 2]
[0094] (Example 3-1) (1) Manufacture of liquid crystal polyester (LCP2) Into a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 1511.1 g (8.03 mol) of 2-hydroxy-6-naphthoic acid, 410.2 g (2.97 mol) of p-hydroxybenzoic acid, 1291.4 g (12.65 mol) of acetic anhydride, and 0.058 g of 1-methylimidazole as a catalyst were placed. After the inside of the reactor was sufficiently replaced with nitrogen gas, the temperature was raised to 140°C over 30 minutes under a nitrogen gas stream, and the temperature was maintained and refluxed for 1 hour. The temperature was then raised to 275°C over 4 hours while distilling off the by-product acetic acid, and the reaction was deemed to be complete when an increase in torque was observed, and the contents were removed. The flow-start temperature of the resulting solid was 217°C. The resulting solid was cooled to room temperature and pulverized in a coarse pulverizer, then heated from room temperature to 200°C over 1 hour in a nitrogen atmosphere, heated from 200°C to 242°C over 7 hours, and held at 242°C for 10 hours to obtain a powdered liquid crystal polyester (LCP2) by solid-phase polymerization.
[0095] The flow initiation temperature of the liquid crystal polyester (LCP2) was measured in the same manner as in Example 1-1 and was found to be 292°C. The liquid crystal polyester (LCP2) had a relative dielectric constant of 3.5 and a dielectric loss tangent of 0.0011 at 10 GHz.
[0096] (2) Preparation and Evaluation of Liquid Crystal Polyester Composition and Pellets A liquid crystal polyester composition was obtained by mixing the liquid crystal polyester (LCP1), the liquid crystal polyester (LCP2) and the glass flakes (G1) in a mass ratio of 55.2:36.8:8. The liquid crystal polyester composition was then granulated at a cylinder temperature of 320°C using a twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd., PCM-30) to obtain pellets of the liquid crystal polyester composition. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 3.
[0097] (Comparative Example 3-1) (1) Preparation and Evaluation of Liquid Crystal Polyester Composition and Pellets A liquid crystal polyester composition was obtained by mixing the liquid crystal polyester (LCP1) and the liquid crystal polyester (LCP2) in a mass ratio of 60:40. The liquid crystal polyester composition was then granulated at a cylinder temperature of 320°C using a twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd., PCM-30) to obtain pellets of the liquid crystal polyester composition. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 3.
[0098] [Table 3]
[0099] (Example 4-1) A resin composition was obtained by mixing liquid crystal polyester (LCP1), glass flakes (G1), and glass fiber (SC3J260S, manufactured by Nitto Boseki Co., Ltd.) in a mass ratio of 87.6:7.6:4.8. The liquid crystal polyester composition was then granulated at a cylinder temperature of 330°C using a twin-screw extruder (PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) to obtain pellets of the liquid crystal polyester composition. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 4.
[0100] (Example 4-2) A resin composition was obtained by mixing liquid crystal polyester (LCP1), glass flakes (G1), and glass fiber (SC3J260S, manufactured by Nitto Boseki Co., Ltd.) in a mass ratio of 83.6:7.3:9.1. The liquid crystal polyester composition was then granulated at a cylinder temperature of 330°C using a twin-screw extruder (PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) to obtain pellets of the liquid crystal polyester composition. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 4.
[0101] (Example 4-3) A resin composition was obtained by mixing liquid crystal polyester (LCP1), glass flakes (G1), and glass fiber (SC3J260S, manufactured by Nitto Boseki Co., Ltd.) in a mass ratio of 70.8:6.2:23. The liquid crystal polyester composition was then granulated at a cylinder temperature of 330°C using a twin-screw extruder (PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) to obtain pellets of the liquid crystal polyester composition. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 4.
[0102] [Table 4]
[0103] (Comparative Example 5-1) (1) Manufacture of liquid crystal polyester (LCP3) A reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer and a reflux condenser was charged with 994.5g (7.2 mol) of 4-hydroxybenzoic acid, 446.9g (2.4 mol) of 4,4'-dihydroxybiphenyl, 299.0g (1.8 mol) of terephthalic acid, 99.7g (0.6 mol) of isophthalic acid and 1347.6g (13.2 mol) of acetic anhydride, and 0.19g of 1-methylimidazole was added as a catalyst. After the inside of the reactor was sufficiently replaced with nitrogen gas, the temperature was raised to 140°C under a nitrogen gas flow over 30 minutes, and the temperature was maintained and refluxed for 1 hour. Then, 0.92g of 1-methylimidazole was added. Thereafter, the temperature was raised to 300°C over 4 hours and 20 minutes while distilling off the by-product acetic acid, and the time when the torque increase was observed was deemed to be the end of the reaction, and the contents were taken out. The flow-start temperature of the obtained solid was 245°C. The obtained solid was cooled to room temperature and crushed in a coarse crusher, and then heated from room temperature to 240°C over 1 hour in a nitrogen atmosphere, heated from 240°C to 284°C over 5 hours and 40 minutes, and held at 284°C for 5 hours, and polymerization reaction was carried out in the solid phase to obtain liquid crystal polyester (LCP3). The flow-start temperature of the obtained liquid crystal polyester (LCP3) was 330°C.
[0104] (2) Preparation and Evaluation of Liquid Crystal Polyester Composition and Pellets The liquid crystal polyester (LCP3) and the glass flakes (G1) were mixed in a mass ratio of 92:8 to obtain a liquid crystal polyester composition. The liquid crystal polyester composition was then granulated at a cylinder temperature of 330°C using a twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd., PCM-30) to obtain pellets of the liquid crystal polyester composition. The obtained pellets were used to carry out the same evaluation as in Example 1-1, and the results are shown in Table 5.
[0105] (Comparative Example 5-2) A liquid crystal polyester composition and pellets were produced in the same manner as in Example 5-1, except that glass flakes (G1) were not added and only liquid crystal polyester (LCP3) was used. The obtained pellets were evaluated in the same manner as in Example 1-1, and the results are shown in Table 5.
[0106] [Table 5]
Claims
1. Contains liquid crystal polyester and glass flakes, The liquid crystal polyester contains a first monomer unit having a condensed aromatic ring and a second monomer unit having a benzene ring, The content of the glass flakes is 1 to 30 parts by mass with respect to 100 parts by mass of the liquid crystal polyester and the glass flakes in total, The density of the glass flakes is 1.8 g / cm 3 2.5g / cm or more 3 A liquid crystal polyester composition, which is:
2. The liquid crystal polyester composition according to claim 1 , wherein the condensed aromatic ring is a naphthalene ring.
3. 2. The liquid crystal polyester composition according to claim 1, wherein the content of the first monomer unit is 50 mol % or more based on the total of all monomer units constituting the liquid crystal polyester.
4. The liquid crystal polyester composition according to claim 1 , wherein the glass flakes have a thickness of 0.1 μm or more and 2 μm or less.
5. The liquid crystal polyester composition according to claim 1, wherein the glass flakes have an average particle size (D50) of 1 μm or more and 50 μm or less.
6. The liquid crystal polyester composition according to claim 1 , wherein the content of the inorganic filler other than the glass flakes is 25 mass % or less.
7. A pellet comprising the liquid crystal polyester composition according to any one of claims 1 to 6.
8. A molded article comprising the liquid crystal polyester composition according to any one of claims 1 to 6, The molded article is a connector, a socket, a relay part, a coil bobbin, an optical pickup, an oscillator, a semiconductor package, an IC tray, a wafer carrier, a home electrical appliance part, a lighting fixture part, an audio product part, a ferrule for an optical cable, a telephone part, a facsimile part, a modem part, a separation claw, a heater holder, an impeller, a fan gear, a gear, a bearing, a motor part, a motor case, an engine part, an engine room part, an electrical component part, an automobile interior part, a microwave cooking pot, a heat-resistant tableware, a flooring material, a wall material, a beam, a pillar, a roofing material, an aircraft part, a spacecraft part, a space equipment part, a nuclear reactor, an offshore facility member, a cleaning tool, an optical equipment part, a valve, a pipe, a nozzle, a filter, a membrane, a medical equipment part, a medical material, a sensor part, a sanitary fixture, a sporting goods, or a leisure goods.
Citation Information
Patent Citations
Liquid crystalline polymer composition
JP2003268252A